2018
DOI: 10.1002/adma.201705611
|View full text |Cite
|
Sign up to set email alerts
|

2D‐Black‐Phosphorus‐Reinforced 3D‐Printed Scaffolds:A Stepwise Countermeasure for Osteosarcoma

Abstract: With the ever-deeper understanding of nano-bio interactions and the development of fabrication methodologies of nanomaterials, various therapeutic platforms based on nanomaterials have been developed for next-generation oncological applications, such as osteosarcoma therapy. In this work, a black phosphorus (BP) reinforced 3D-printed scaffold is designed and prepared to provide a feasible countermeasure for the efficient localized treatment of osteosarcoma. The in situ phosphorus-driven, calcium-extracted biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
299
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(306 citation statements)
references
References 59 publications
6
299
0
1
Order By: Relevance
“…When the BP‐functionalized NE gels are implanted into bone defect regions, it appears that the BP nanosheets first recruit bone forming cells to the area and subsequently serve as an anchor to absorb the signaling molecules secreted by the recruited cells for initiating bone formation. Simultaneously, the continual release of phosphate acid into the network by the BP nanosheets could coordinate large amounts of secreted calcium ions, leading to the slow formation of a CaP complex that adheres to the polymer network and induces bone tissue ingrowth . The deposited signaling molecules and biomineralized CaP mimics the ECM microenvironment, providing a surface for cell attachment and promoting differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the BP‐functionalized NE gels are implanted into bone defect regions, it appears that the BP nanosheets first recruit bone forming cells to the area and subsequently serve as an anchor to absorb the signaling molecules secreted by the recruited cells for initiating bone formation. Simultaneously, the continual release of phosphate acid into the network by the BP nanosheets could coordinate large amounts of secreted calcium ions, leading to the slow formation of a CaP complex that adheres to the polymer network and induces bone tissue ingrowth . The deposited signaling molecules and biomineralized CaP mimics the ECM microenvironment, providing a surface for cell attachment and promoting differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that inorganic phosphate plays an important role in promoting biomimetic calcium phosphate crystal mineralization, which enhances bone cell adhesion, proliferation, and differentiation . Moreover, recent studies have demonstrated that the degradation products of BP nanosheets under physiological conditions could be in situ transformed into calcium phosphate nanoparticles capable of improving the bone regeneration process . Nevertheless, using bioactive BP nanosheets as biodegradable composites to regulate the mineralized process and bioactivity of tough DN hydrogels for bone regeneration has not been previously explored.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced technology is used to fabricate artificial scaffolds used for bone regeneration . Yang et al integrated 2D BP nanosheets with 3D printed bioglass (BG) scaffolds to construct a therapeutic platform. The authors obtained a BP–BG scaffold to remove osteosarcoma by PTT and then repaired bone regeneration in situ ( Figure ).…”
Section: Biomedical Applications Of Bpmentioning
confidence: 99%
“…Copyright 2018, Wiley‐VCH. 3D printing image: Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, photothermal therapy was developed using various photothermal agents such as gold nanoparticles, graphene, MoS 2 , and organic nanoparticles to generate effective tumor inhibition meanwhile to decrease the side‐effect, due to its high spatio‐temporal operation, noninvasion, and low‐toxicity . Few studies further introduce photothermal agents into bioactive scaffolds to combine local photothermal therapy with tissue engineering, which was expected to simultaneously achieve enhanced healing of large tissue defects after surgical resection and effective killing of residual tumor cells . Although this strategy opened a window for integration of tumor therapy and tissue regeneration to solve the sequel caused by surgery intervention, conventional photothermal agents combined scaffold were all designed as sustained heat sources under irradiation regardless of their location, which may cause serious random damages to the preseeded stem cells, even the normal tissues surrounding tumor, during photothermal therapy .…”
Section: Introductionmentioning
confidence: 99%